2013
DOI: 10.4103/0971-4065.120343
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous pyelonephritis: Outcome with conservative management

Abstract: Emphysematous pyelonephritis is a life-threatening condition characterized by necrotising gas forming infection of the renal parenchyma. We describe eight patients seen over a period of 2 years, 62.5% males and 37.5% females with age range between 21 and 65 years. About 75% patients had diabetes mellitus. Six patients were managed conservatively. One patient required nephrectomy with percutaneous drainage and one patient died without surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 8 publications
1
16
0
9
Order By: Relevance
“…In contrast, other studies suggested that PCD is a quite effective and adequate approach with a high success rate even in extensive EPN. [ 3 4 11 12 13 14 15 16 22 23 ] which is in accordance with our study where patients managed conservatively had a good outcome and survived. Furthermore, two patients with class I and class IV treated primarily with DJ stent showed improvement similar to those treated with nephrostomy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, other studies suggested that PCD is a quite effective and adequate approach with a high success rate even in extensive EPN. [ 3 4 11 12 13 14 15 16 22 23 ] which is in accordance with our study where patients managed conservatively had a good outcome and survived. Furthermore, two patients with class I and class IV treated primarily with DJ stent showed improvement similar to those treated with nephrostomy.…”
Section: Discussionsupporting
confidence: 92%
“…[ 3 ] Furthermore, it is commonly seen in patients with obstructive uropathy, polycystic kidney, and end-stage renal disease. [ 4 ] With a mortality rate of 25%;[ 5 ] it is considered life-threatening, which, necessitates early and aggressive management. [ 6 ] The management can be classified into: Conservative which includes medical and minimally invasive procedures, such as percutaneous drainage (PCD) (nephrostomy) or double J (DJ) stent, and surgical which is nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However there are growing reports of successful medical treatment of EPN. [12][13][14][15] According to these reports, our case could be considered treatable by antibiotics alone partly because of the rapid diagnosis and the adequate therapy provided.…”
Section: Discussionmentioning
confidence: 99%
“…Emphysematous pyelonephritis (EP) is an acute necrotizing infection complicated by gas formation within the renal parenchyma. 1 Four factors lead to risk for EP: high blood glucose, poor tissue perfusion, the presence of gas forming bacteria, and immunosuppression. E. coli is the pathogen in most cases.…”
Section: Discussionmentioning
confidence: 99%